2018
DOI: 10.2478/folmed-2018-0028
|View full text |Cite
|
Sign up to set email alerts
|

Histological Gingival Assessment after Conventional and Laser Gingivectomy

Abstract: Background: Gingivectomy is a procedure often performed in everyday clinical practice using numerous instruments. Aim: To evaluate and compare the gingival cut surface after gingivectomy with 6 different surgical instruments – a surgical scalpel, an Er:YAG laser, a CO2 laser, a ceramic bur, an electrocautery device, and a diode laser. Materials and methods: Gingivectomy using the above listed instruments was performed in 18 patients. The histological samples excised with a surgical scalpel were assigned as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
2
10
0
1
Order By: Relevance
“…The clinical study findings correspond to independent histological study [11], with results leading to the same conclusions. Future collaboration could be beneficial for the scienc in the field of periodontal laser treatment.…”
Section: Discussionsupporting
confidence: 85%
“…The clinical study findings correspond to independent histological study [11], with results leading to the same conclusions. Future collaboration could be beneficial for the scienc in the field of periodontal laser treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Currently, the main laser types available for gingivectomy are semiconductor diode laser, CO 2 laser, Nd:YAG laser, Er:YAG laser, and Er,Cr:YSGG laser ( 16 19 ). Among these types, except the first one (semiconductor diode laser), the others are all capable of performing soft-tissue cutting and function to achieve hemostasis and sterilization ( 17 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…in dental treatments, HLLT has been used in surgical treatments (1) of the gingiva (10) and for dental implants (11). We recently demonstrated that LLLT can induce bone formation and proposed the use of CO 2 lasers for bone regeneration therapy as a new method of laser-induced bone therapy (3).…”
Section: Effects Of Irradiation By Carbon Dioxide Laser Equipped With...mentioning
confidence: 99%